Use of Hybrid Phase Shifter for Congestion Management in A Grid with RESs and EVs: Transmission Efficiency Benefit in Comparison with Phase Shifting Transformer - Salah Eldeen Gasim Mohamed (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
Integration of renewable energy sources (RESs) and electric vehicles (EVs) to electric power grids is increasing. These RESs and EVs may introduce major problems to grid such as transmission lines congestion. Owing to the causative factors nature, congestion may regularly happen and continue forlong commulative time. Thus, transmission efficiency (TE) is a major factorwhen relieving congestion. Congestion can be relieved by using phase shifting transformers (PSTs), hybrid phase shifters (HPSs), or flexible AC transmission system (FACTS) devices. However, PSTs have technical drawbacks such as their large steps, which may result in increased losses, and FACTS devices cost is high. This paper investigates benefits of using an HPS rather than a PST in terms of TE. As HPS operates continuously, it provides more precise control of active power flow than PST. A modified IEEE-14 bus test system is used and a security margin is kept in each simulated case with HPS/PST. Results revealed higher TE when an HPS is used. Thus, RESs and EVs can be more optimally hosted with HPSs.Keywords: electric vehicles, grid flexibility, hybrid phase shifter, phase shifting transformer, renewable energy sources, transmission efficiency.